Peran Orang Tua, Masyarakat dan Guru terhadap Motivasi Belajar Siswa SDN 03 Sukadana - Aep Saefullah; Neila Aisha; Asep Surya Lesmana; Nyimas Ema Holiza; Khoirul Ibad (Departement of Mathematics Education, 2023)
The study aims to determine how the role of parents, community and teachers on student learning motivation at SDN 03 Sukadana, Ciawigebang sub-district, Kuningan district. The study used a descriptive qualitative method. The object of research took 40 respondents consisting of parents, community, and teachers. Data processing techniques were carried out with field observations, interviews and literature studies. The research was conducted during 5 months ranging from August to December 2022. The results showed that parents or guardians of SDN 03 Sukadana students have an important role in student learning motivation. Parents as facilitators of children learning outside the hours of school teaching and learning activities Parents have a high awareness in developing spurring student learning motivation. They monitor, accompany and supervise their children's learning process at home. The surrounding community at SDN 03 Sukadana is active in the progress of students' learning motivation and the learning process at school. Teachers at SDN 03 Sukadana play a significant role in student learning motivation. Teachers need to strengthen their human resources in terms of utilizing and using technology to support student learning.